Factors that affect the readiness of human resource management in employing people with disability: Hotel Industry in Kota Kinabalu, Sabah, Malaysia / Siti Nuraihana Awang Rajip and Asri Salleh - Awang Rajip, Siti Nuraihana; Salleh, Asri (2021)
More than a billion people in the world are estimated to live with some sort of disability. This corresponds to about 15% of the world's population (World Health Organization, 2020). The numbers are also increasing due to the aging population and chronic health conditions. According to the World Health Organization, there was an unstated presumption that employers would not hire people with disabilities if quotas were not in place because of lower productivity, increased costs of labour such as accommodations and facilities, and even discrimination against people with disabilities. According to the study made by Leng and Ta (2013), the presence of bias and misunderstandings among the public about the disabled individuals' capacity to execute and finish the duties assigned to them causes them to remain jobless. With a particular emphasis on the hospitality sector, human resource professionals have the same reservations about hiring people with disabilities because they believe that disabled people are unable to perform the tasks assigned to them and that providing accommodations for this group will cost a lot of money. Khoo et. Al (2013) found that most businesses in the restaurant and hotel industries were reluctant to recruit handicapped or disabled individuals because of the additional costs that they would have to incur to accommodate them. Besides, Hui, Tsui, and Tavitiyaman (2020) mentioned that disabled people were emotionally unstable at work, slowed in doing their job, had uncertain performances, and received too many complaints from the customers which resulted in a lower impression of the hotel. This is being supported by study previous study whereby Barber, Madera, and Taylor (2019) mentioned that services given by disabled people were rated lower specifically on their competencies than services given by nondisabled people. Lacking in terms of necessary knowledge, skills, abilities, and other characteristics mainly resulted in the lack of employment among disabled people as contact between customers and workers is very crucial in the hospitality industry. In addition to that, failure to recognise and take advantage of government incentives may also contribute to the low employment rates among persons with disabilities, which is still a significant problem. Hence, the purposes of this study are to determine to what extent barrier-free environment and facilities, disability awareness training, and incentives introduced by the Malaysian Government affected the hospitality's Human Resource Management decision in employing people with disabilities.